Edible bird’s nest enhances antioxidant capacity and increases lifespan in Drosophila Melanogaster - Hu, Q; Li, G; Yao, H; He, S; Li, H; Liu, S; Wu, Y; Lai, X (Cellular and Molecular Biology, 2016)
In this study, we aims to investigate the effects of edible bird’s nest (EBN) on anti-aging efficacy. In order to investigate lifespan and mortality rate of flies, we treated flies with various doses of EBN. Besides, fecundity, water content and food are determined and heat-stress test is conducted after flies treating with different medium. Effects of EBN on total antioxidant activity (T-AOC), super-oxide dismutase activity (SOD), catalase activity (CAT), and malondialdehyde (MDA) were examined in drosophila melanogaster. Results indicated that flies in EBN treated group illustrated significantly lower mortality rates and longer median and maximum lifespan compared to control group (P<0.05). The fecundity in EBN-treated group was increased compared to control group. SOD levels and CAT activity were significantly increased, and MDA levels decreased in EBN-treated group compared to control group (P<0.01). In conclusion, EBN can extend lifespan, decrease mortality rate and increase survival rate in heat-stress test, and which can also promote SOD and CAT activity and reduce MDA levels. EBN is able to delay drosophila melanogaster aging, attributing to the increasing antioxidant enzyme activities and decreasing content of lipid peroxidation products in drosophila melanogaster.